Cyberlindnera dasilvae sp. nov., a xylitol-producing yeast species isolated from rotting wood and frass of cerambycid larva. Issue 9 (8th September 2021) - Barros, Katharina O.; Souza, Rafael M.; Palladino, Fernanda; Cadete, Raquel M.; Santos, Ana Raquel O.; Goes-Neto, Aristóteles; Berkov, Amy; Zilli, Jerri E.; Vital, Marcos J. S.; Lachance, Marc-André; Rosa, Carlos A.
Abstract : Six yeast isolates were obtained from rotting wood samples in Brazil and frass of a cerambycid beetle larva in French Guiana. Sequence analysis of the ITS-5.8S region and the D1/D2 domains of the large subunit rRNA gene showed that the isolates represent a novel species of Cyberlindnera . This novel species is related to Cyberlindnera japonica, Cyberlindnera xylosilytica, Candida easanensis and Candida maesa . It is heterothallic and produces asci with two or four hat-shaped ascospores. The name Cyberlindnera dasilvae sp. nov. is proposed to accommodate the novel species. The holotype of Cy. dasilvae is CBS 16129 T and the designated paratype is CBS 16584. The MycoBank number is 838252. All isolates of Cy. dasilvae were able to convert xylose into xylitol with maximum xylitol production within 60 and 72 h. The isolates produced xylitol with values ranging from 12.61 to 31.79 g l −1 in yeast extract–peptone–xylose medium with 5% xylose. When the isolates were tested in sugarcane bagasse hydrolysate containing around 35–38 g l −1 d -xylose, isolate UFMG-CM-Y519 showed maximum xylitol production.